Effects of liraglutide or lifestyle interventions combined with other antidiabetic drugs on abdominal fat distribution in people with obesity and type 2 diabetes mellitus evaluated by the energy spectrum ct: A prospective randomized controlled study - Yu, Dongni; Zou, Mingzhu; Pan, Qi; Song, Yan; Li, Miao; Zhang, Xianbo; Zhou, Yan; Wang, Xiaoxia; Guo, Lixin (Frontiers in Endocrinology, 2022)
Objective: To study the effects of liraglutide or lifestyle interventions combined with other antidiabetic drugs on glucose metabolism and abdominal fat distribution in patients with obesity and type 2 diabetes mellitus (T2DM). Methods: From April 30, 2020, to May 30, 2022, a prospective randomized controlled study was carried out at the Endocrinology Department of Beijing Hospital, the National Center of Gerontology. According to the in- and exclusion criteria and by the random table method, revisited T2DM patients were selected as the research subjects and were allocated into a Study group (taking liraglutide) and a Control group (underwent lifestyle interventions). All patients received continuous 12-weeks interventions to the endpoint, and the changes of value [Δ=(endpoint)-(baseline)] of physical measurements, blood tests, the energy spectrum CT examination results, and body composition analysis results were analyzed and compared. Results: A total of 85 people completed this study, and among them, 47 were in the Study group and 38 were in the Control group. Compared with the Control group, the changes of hemoglobin A1c (HbA1c) level (-0.78±1.03% vs. -1.57±2.00%, P=0.025), visceral fat area (0.91±16.59 cm2 vs. -7.1±10.17 cm2, P=0.011), and subcutaneous fat area of abdomen [0 (-18.75, 15.5) cm2 vs. -16.5 (-41.75, -2.25) cm2, P=0.014] were all greater in the Study group. The adverse events caused by liraglutide were mainly concentrated in the gastrointestinal system and all of them were minor adverse events. Conclusion: Liraglutide can be the drug of choice for weight management and reduction of abdominal fat distribution in patients with obesity and T2DM.